Inventory of Macrofungi in Area of Taman Hutan Raya (TAHURA) Ir. H. Djuanda Bandung - Suryani, Yani; Cahyanto, Tri; Akbar, Rahmat Taufiq Mustahiq; Dicky, Dicky; Madani, Pameila Qaulan Tsaqila; Meldania, Rindi; Tisnawati, Sophia Eka; Darniwa, Adisty Virakawugi; Musa’adah, Musa’adah; Fitriyyah, Ita; Tridesianti, Siska; Adawiyah, Ayuni (Journal of Tropical Biodiversity and Biotechnology, 2024)
Taman Hutan Raya (TAHURA) Ir. H. Djuanda Bandung is an integrated conservation area in which there are secondary natural forests that have various kinds of flora and fauna. Macrofungi are fungi whose fruiting bodies can be seen directly without the aid of a microscope, heterotrophic, and ecologically act as decomposers of organic matter (decomposers) and as biological control agents. Data related to research results on macrofungi in the Tahura area is still limited and need more comprehensive research. This study aimed to inventory, determine the growth factors, and potential utilization of macroscopic fungi. Observations were carried out during the period of November 2021 - April 2022 using exploration method. Sampling was done by purposive sampling method. Macrofungi identification process was carried out based on morphological characters such as cap, stalk, and lamella, The environmental factors observed included air humidity, soil pH, temperature, and type of substrate. The results showed that as many as 83 species were found in the Protection block, 50 species were found in the Collection block, and 99 species were identified in the Utilization block from the phyla Basidiomycota and Ascomycota. The macrofungi found have potential as biodegradation agents, food ingredients, non-food ingredients, drugs, antimicrobials, antioxidants, anticancer, and anti-inflammatory.